2016
DOI: 10.1111/edt.12311
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and seven storage media on human periodontal ligament fibroblast viability

Abstract: SMilk was the best storage medium, followed by WMilk and HBSS. Coconut, Propolis, and Egg can be indicated for the conservation of PDLF up to 3 h. The lower temperature (5°C) undermined the effectiveness of HBSS and favored SMilk and WMilk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 35 publications
0
26
0
2
Order By: Relevance
“…A further three studies also recommend milk and HBSS along with different natural products . Twenty‐one studies recommended milk in some form in addition to the other media tested, while 13 of these studies exclusively recommended milk . HBSS was found to be the second most recommended individual medium in 16 studies .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A further three studies also recommend milk and HBSS along with different natural products . Twenty‐one studies recommended milk in some form in addition to the other media tested, while 13 of these studies exclusively recommended milk . HBSS was found to be the second most recommended individual medium in 16 studies .…”
Section: Resultsmentioning
confidence: 99%
“…The recommendation for coconut water is based on the maintenance of PDL cell viability, cost‐effectiveness, and ease of availability. Coconut water may be easily accessible in some parts of the world, and this would make it a viable storage medium in case of an avulsion for some geographic locations. However, it cannot be recommended universally due to the practical limitations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Moreira‐Neto et al found that CW was not a suitable storage media when tested on fibroblasts from the knee joint. More recently, de Souza et al reported inferior viability with CW in comparison with skimmed and whole milk with limited ability to conserve PDL cells for up to 3 hours only. These findings may be mainly explained by using CW from early stages of maturity with low pH and the difference in fibroblast cells phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…CW also contains different antimicrobial peptides that are effective against some pathogenic bacteria . The use of CW as a storage medium has been widely investigated, but with controversial results . The exact composition of CW has been related to the stage of maturation of the coconut and the region where the coconut palms grow .…”
Section: Introductionmentioning
confidence: 99%
“…Several natural and artificial solutions such as green tea extract, coconut water, aloe vera extract, saliva, milk, Propolis, Gatorade, Viaspan, Ricetral, and emdogain have been evaluated as storage media . In addition to pasteurized milk, powdered milk and milk substitutes have been widely recommended as suitable short‐term storage media for an avulsed tooth because of their ability to preserve PDL cells . However, when compared to HBSS or DMEM, none of them could be considered as an ideal storage solution due to their mixed efficacy .…”
Section: Introductionmentioning
confidence: 99%